IDENTIFIKASI TANTANGAN DALAM PENERAPAN GREEN BUILDING DI JAKARTA - Xavieri Linggo, Johannes Christophorus; Sutandi, Arianti (JMTS: Jurnal Mitra Teknik Sipil, 2023)
The concept of green building is one way to address global warming. In Indonesia, the number of buildings implementing green building concepts is still very limited. The government has implemented several regulations related to green building concepts, but there are still challenges such as lack of information, inadequate financial incentives, and awareness programs by the government and other relevant authorities. This study aims to identify the barriers faced in the implementation of green building in Indonesia, specifically in DKI Jakarta, to determine the underlying constraints in the development of green building in the country. Questionnaires for this research were distributed to consultants and developers in Jakarta. The research findings indicate that there are six factors constraining green building implementation, namely regulation, government, finance, technical, technology, and education. The top three indicators that pose challenges in implementing green building in Jakarta are the requirement for certification of experts as proof of their expertise, the high financial risks associated with green building, and the significant costs involved in green building construction. Abstrak Konsep green building adalah salah satu cara untuk mengatasi pemanasan global. Di Indonesia jumlah bangunan yang menerapkan konsep green building masih sangat sedikit. Pemerintah sudah membuat beberapa peraturan yang berkaitan dengan konsep green building, namun masih terdapat tantangan seperti kurangnya informasi, kurangnya insentif keuangan dan program kesadaran oleh pemerintah dan otoritas terkait lainnya. Penelitian ini bertujuan untuk mengidentifikasi hambatan-hambatan yang dihadapi dalam penerapan green building di Indonesia khususnya di DKI Jakarta, sehingga dapat diketahui kendala mana yang menjadi dasar dalam pengembangan green building di Indonesia. Kuesioner untuk penelitian ini disebar ke konsultan dan developer yang ada di Jakarta. Hasil penelitian menunjukan bahwa terdapat 6 faktor yang menjadi kendala, yaitu; regulasi, pemerintah, finansial, teknis, teknologi, dan pendidikan. 3 peringkat indikator tertinggi yang menjadi kendala dalam penerapan green building di Jakarta adalah dalam pelaksanaan dibutuhkan sertifikasi bagi tenaga ahli sebagai bukti bahwa SDM tersebut ahli dalam bidangnya, Green Building memiliki risiko keuangan yang besar, dan Green Building menghabiskan banyak biaya.